Sex-specific associations among infant food and atopic sensitizations and infant neurodevelopment - Rodriguez, Nicole; Tessier, Carmen A.; Mandhane, Piushkumar J.; Pei, Jacqueline; Simons, Elinor; Moraes, Theo J.; Turvey, Stuart E.; Subbarao, Padmaja; Kozyrskyj, Anita L. (Frontiers in Pediatrics, 2022)
Introduction Food sensitization is a first and strong indicator of immune deviation in the progression to other allergic conditions. Sensitization to food or other allergens and related inflammation during critical windows of infant development may adversely affect neurodevelopmental milestones. However, additional research is needed to test this association further. Methods Associations between atopic (any food or aeroallergen) or food sensitization (specific to egg, soybean, peanut, and milk) at age 1 year and neurodevelopment up to 2 years of age were evaluated in the national CHILD Cohort Study, with a secondary aim examining whether these associations were sex-specific. Food and atopic sensitization were assessed by skin prick tests (SPT) in 1-year-old infants, with neurodevelopment assessed using the cognitive, language, motor, and social-emotional subscales of the Bayley Scales of Infant Development (BSID-III) administered at 1 and 2 years of age. Results Atopic sensitization was present among 16.4% of infants, while 13.4% had food sensitizations. Only socioemotional scores reached statistical significance among the four BSID-III domains. Both atopic and food sensitization at 1 year of age was associated with lower social-emotional scores, independent of the infant's ethnicity. These findings were sex-specific and only observed among boys, among whom social-emotional scores were lowered by 5 points if atopic sensitization was present (−5.22 [95% CI: −9.96, −0.47], p = 0.03) or if food sensitization was present (−4.85 [95% CI: −9.82,0.11], p = 0.06). Similar results were observed using the standard SPT cut-off of ≥3 mm — for atopic sensitization (−5.17 [95% CI: −11.14, −0.80], p = 0.09) and for food sensitization (−4.61 [95% CI: −10.96, 1.74], p = 0.15). Conclusion In our study of term infants, we found an inverse, cross-sectional association between atopic and food sensitization status and social-emotional development scores in male children but not female children.